(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Saffron has been considered an invaluable medicinal and fragrant spice cocaine in folk medicine, and the beneficial properties of its plant for human health have long been known. To date, information about the healing properties of the plant and methods of their use has been studied in the world of science.